Contract Management Contractual Performance, Renegotiation, and Claims: How to Safeguard and Increase Profit Margins - Brunet, Alain; César, Franck (Law for Professionals, 2021)
This book presents the latest findings relating to behavioral economics and the digital tools applied to contract management. There has been a decisive change in the role of contracts in the past decade, with contracts being transformed from purely legal necessities designed to protect against worst-case scenarios into tools for optimizing ongoing and mutually profitable business relationships with customers. There is an increasing emphasis on tight contracts, where time-risk and additional costs are passed on to the prime contractor, who may suffer heavy penalties in the event of non-performance. Contracts shape the behavior of the parties involved and as such have a major impact on project success. The contract manager's goals are to protect the interests of the company and its shareholders by minimizing the company's financial and contractual liabilities and to maximize its profitability while ensuring end-user satisfaction.